(untitled) (Philological Studies, 2019)
Each language has a wide number of phrases which comprise a very important part of the lexical stock of the language. In the Czech and Macedonian phraseology there is a range of interlingual parallels, common features in the content and form, which are explained both on genetic and typological basis. The phrases which are going to be presented in this paper are the somatic phrases which consist the word ’eye’ as a component. For these phrases it can be said that are the ones of the most frequent in everyday communication. The paper focuses on part of the phrases having the component ’eye’ both in Macedonian and Czech language. As a result of their juxtaposition in regard to the manner of expressing the same meaning in both languages, the phrases can be divided in three groups: 1. The component ’eye’ is present both in Macedonian and Czech language and the respective meaning is expressed in the same manner, with same language terms. 2. The component ’eye’ is present in both languages, but the meaning is not expressed with the same terms. 3. The third group can be divided in two sub-groups as follows: a) the component ’eye’ is not present in one of the languages, but some element of the phrase is related with the function of the eye to see; b) the component ’eye’ is not present in one of the languages and the respective meaning in the other language is expressed in completely different way. Based on the analyzed examples, it can be concluded that both language are very rich in phrases inspired by the eye as part of the human body. The analysis shows the closeness in the associative- pictorial thought of the speakers of both languages – Macedonia and Czech. Therefore, the study of this layer of phraseology, especially in regard to the juxtaposition of Slavic languages is of exceptional interest.